(untitled) (8gen-ART, 2025)
In ancient and modern times, women have shed light on their times in every field. There, she was a sultan, a judge, a poet, an artist, a writer, a lawyer, a warrior, and one of the narrators of the prophetic hadiths. Also, until now, women still work and contribute with all their energy to the maintenance of their homes and family members. They are wives, mothers, sisters, and daughters, and this is what makes the role women play in building society important. It is a role that cannot be ignored or underestimated. Through our research that addresses the issue of violence against women within the family between the socialization process and male authority, we see that the phenomenon of violence against women is one of the phenomena that has historical, cultural and social dimensions. It is not limited to time and space. It is not related to the nature of society, whether conservative, western or eastern, but to the existence of man and the mutual relations between men and women within the family. I applied this research to ten immigrant women who were abused in Isparta province of Turkey and used the case study approach using qualitative research. I used interview and observation tools as methods. Then I analyzed these cases and obtained results that were suitable for the purpose of the research.